Estudo do efeito modulador do macrolídeo tilosina na reação inflamatória aguda de tilápias do Nilo (Oreochromis niloticus), vacinadas e desafiadas com Streptococcus agalactiae - Faria, Vanessa Pavesi de [UNESP] (2015)
This study evaluated the effect modulator tylosin on hematologic response of tilapia, administered orally in feed, on acute inflammatory response of Nile tilapia, O. niloticus, vaccinated and challenged with S. agalactiae. 104 tilapia (± 300 g) were placed randomly in 13 aquariums (n = 8), constituting four treatments: PF = Standard Saline (n = 8); + V NT = not treated with tylosin and vaccinated (n = 24); NV + NT = Not treated with tylosin and non-vaccinated (n = 24); T + V = treated with tylosin and vaccinated (n = 24); T + = NV treated with tylosin and non-vaccinated (n = 24). The bacterin of S. agalactiae (1,0x109 cells / ml) was intramuscularly administered 15 days before the bacterial challenge. The aerocistite study showed an increase in cell migration number as the evolution of the inflammatory response (P <0.001) with peak accumulation in 48 of the HPD. Fish vaccinated showed greater number of cells in the inflammatory exudate 6 and 48 HPD. At the beginning of the inflammatory reaction (6 HPD), fish vaccinated and treated with tylosin showed leukocytosis with a marked absolute lymphocytosis on monocyte and neutrophil relative and absolute. Late 48 HPD, these animals recovered the leukocyte values, with scores close to those seen in control animals (PF). In the initial phase 6 HPD, tilapia had microcytosis, increased creatinine, the enzymatic activity of alkaline phosphatase and aspartate aminotransferase, and changes in energy metabolism with decreased cholesterol, increased triglycerides and glucose. With the evolution of the infection HPD 24 and 48, there was macrocytosis, decreases in hemoglobin and red blood cell counts, these responses are affected by treatment with tylosin. Triglycerides and cholesterol returned to baseline levels in vaccinated animals and occurred earlier recovery of creatinine and alkaline phosphatase changes in vaccinated and treated with tylosin tilapia. Vaccinated tilapia and untreated showed ...